1997
DOI: 10.1183/09031936.97.10071585
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind randomized trial of nicotine nasal spray as an aid in smoking cessation

Abstract: A double-blind randomized trial of nicotine nasal spray as an aid in smoking cessation. T. Blöndal, M. Franzon, A. Westin. ERS Journals Ltd 1997. ABSTRACT: The objective of the study was to evaluate the therapeutic efficacy of nicotine nasal solution (NNS) for smoking cessation from the stopping day up to 3 months. We also followed the participants for 2 yrs after ceasing smoking to assess what happens after stopping using NNS.In a placebo-controlled, double-blind, 2 yr prospective study, 157 smokers were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 16 publications
1
33
0
2
Order By: Relevance
“…FTND = Fagerström Test for Nicotine Dependence. (Blondal et al, 1997;Garvey et al, 2000;Hajek et al, 1999;Hurt et al, 1997;Killen et al, 2004;Lam et al, 2005;Mooney et al, 2007;Schmitz et al, 2007;Shiffman et al, 2008). Adherence data for the COMPASS trial were collected prior to the Federal Drug Administration issuing a black box warning about possible neuropsychiatric symptoms associated with varenicline in 2009 and therefore may overestimate future adherence rates for this medication.…”
Section: Discussionmentioning
confidence: 99%
“…FTND = Fagerström Test for Nicotine Dependence. (Blondal et al, 1997;Garvey et al, 2000;Hajek et al, 1999;Hurt et al, 1997;Killen et al, 2004;Lam et al, 2005;Mooney et al, 2007;Schmitz et al, 2007;Shiffman et al, 2008). Adherence data for the COMPASS trial were collected prior to the Federal Drug Administration issuing a black box warning about possible neuropsychiatric symptoms associated with varenicline in 2009 and therefore may overestimate future adherence rates for this medication.…”
Section: Discussionmentioning
confidence: 99%
“…155 None of the four trials reporting continuous abstinence reported point prevalence abstinence. 132,133,157,160 All of the included studies used biochemical verification to confirm non-smoking status.…”
Section: Definition Of Abstinencementioning
confidence: 99%
“…Of the 16 included trials, eight reported methods used to generate their randomisation sequence, with five using computer-generated lists, 130,132,133,159,160 one stratified randomisation 162 and two block randomisation. 131,154 Only seven studies reported using an adequate method for allocation concealment, using centrally performed systems.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This method results in more rapid peak increases in blood nicotine and absorption in the brain, similar to the effects of cigarette smoking (Henningfield and Keenan, 1993). Four placebo controlled clinical trials of NS have demonstrated quit rates comparable to TN (Blondal et al, 1997;Hjalmarson et al, 1994;Schneider et al, 1995;Sutherland et al, 1992). In a meta analysis, the quitting odds ratio for NS vs placebo was 2.9, compared with 2.1 for TN vs placebo (Silagy et al, 1994).…”
Section: Overview Of Smoking Cessation Treatmentsmentioning
confidence: 99%